Misallocation and Productivity in Colombias Manufacturing Industries - Adriana Camacho; Emily Conover (Inter-American Development Bank (IDB), 2010)
Following Hsieh and Klenow (2009), this paper studies productivity dispersions in Colombian industrial establishments using the Colombian Annual Manufacturing Survey (AMS) from 1982 to 1998. The United States is used as a benchmark to estimate the reallocation of capital and labor to equalize marginal products across plants in Colombia. Gains are found in manufacturing Total Factor Productivity (TFP) of approximately 3-8 percent and TPF is positively correlated with exporting status, age, size, and location in the central region of the country. There is also suggestive evidence that opening the economy in 1991 is associated with an increase in plant productivity levels for firms that export goods. The 1990 reform that reduced dismissal costs is associated with an increase in productivity, while the reform that increased labor costs in 1993 is associated with a decrease in plants productivity. Further work is needed to establish a causal relation between productivity and policy changes.
Keywords: D24; O47; 330; Total Factor Productivity; Industry; Reallocating factors of production; Colombia